Colour Sensor White Balance Influence on White-Light Interferometer Resolution - Kalyanov, A.; Lychagov, V.; Smirnov, I.; Ryabukho, V. (ALT Proceedings, 2026)
Impact of a sensor color balance on white-light fullfieldoptical coherence tomography (FF-OCT)resolution is investigated in the paper. Full width athalf magnitude (FWHM) of a coherence pulse wascalculated for various white balance (WB) settings.Simulated dependence of FWHM on WB of asensor and experimental data are shown in thepaper. The minimum interference pulse width canbe achieved by the proper color balance coefficientschoice. And in this case the pulse is narrower thaneither one registered by colour image sensor withWB based on light source emission spectrum or bymonochrome image sensor.